Organized Crime : Culture, Markets and Policies - Organized Crime : Culture, Markets and Policies (Springer, 2008)
Complex interactions of economic, technological, political, and cultural factors have fed the rise of criminal networks worldwide. The contributors provide up-to-date understanding of various aspects of organized crime, in both classic areas of research (drugs, sex trafficking, labor racketeering) and emerging areas of interest (diamod smuggling, money laundering, eco-crime), in locales as varied as Italy, Queber, the Sinai, Bulgaria, and the world's tropical rain forests. Topic are explored from a variety of perspectives, including sociology, criminology, political science, and antropology, giving this book empirical breadth and depth rarely seen in the literature.